QUANTIFYING THE UNKNOWN: A MONTE CARLO APPROACH TO COST CONTINGENCY AND RISK ASSESSMENT - Chauhan, Neeraj (International Journal of Engineering Technologies and Management Research, 2025)
This paper aims at establishing an understanding on how Monte Carlo simulation can be used as a tool for assessing cost contingencies and risks in project management. This method helps to model numerous possible scenarios of unpredictable factors that impact risks so as to carry out the evaluation of the probable impacts on cost estimations. The research also shows how Monte Carlo can be used to model the randomness in the cost factor of a project and therefore provide important insights into the exercises that can be used in managing risks. Drawing upon various case studies, this paper explores how Monte Carlo simulation enhances the level of accuracy in cost estimate, identifies potential cost overruns and strengthens the project planning and control. It is for this reason that this approach can be of so much help in reducing the uncertainties that are likely to surround the financial aspect as well as increase the chances of success in a project.